Arab women's educational leadership and the implementation of social justice in schools. Issue 1 (22nd November 2017) - Arar, Khalid
Abstract : Purpose: The purpose of this paper is to focus on gender and social justice (SJ) among pioneer female principals and superintendents in the Arab education system in Israel. The research questions were: what motivated these women to act for SJ? Are there common personal characteristics and educational values which characterize these women? What actions have they taken to apply SJ through their work? Design/methodology/approach: Four superintendents and two principals participated in in-depth interviews, describing their careers in education and their contributions. Findings: The findings indicate that these women were highly motivated often by their backgrounds to right social wrongs upholding values of equality and justice and empowering others to succeed. They employed leadership skills that initiate a strong desire to succeed and challenged inegalitarian rules and norms. They brought their unique feminine strengths and experience to promote social goals far beyond requirements of their official job descriptions. Hopefully their views and actions can guide the Arab education system to pedagogy that rectifies social injustice includes students and empowers teachers. Originality/value: It is concluded that through their jobs these women leaders were able to initiate a policy of change and promote a new educational agenda.